Comparative Hemolytic Activity of Vibrio parahaemolyticus and Related Vibrios - Twedt, Robert M. (1970)
The hemolytic activities of 91 strains of Vibrio parahaemolyticus isolated from human diarrheal stools, sea fish, and sea water; 21 suspected V. parahaemolyticus cultures isolated from wound infections; 14 nonpathogenic marine vibrios; and 21 V. parahaemolyticus isolated from moribund blue crabs Callinectes sapidus were compared. Potentially pathogenic V. parahaemolyticus strains could be differentiated from the related nonpathogenic marine vibrios, because the former hemolyzed hamster, sheep, and human blood, whereas the latter were nonhemolytic. In addition, V. parahaemolyticus isolated from tissue infections could be differentiated from those of the first group isolated from sea fish or human stools, because the former exhibited primarily an α-hemolytic reaction on chicken blood; the latter exhibited mostly β. It is suggested that V. parahaemolyticus isolated from blue crabs may be differentiated from the first group on the basis of their hemolysis of human blood. A useful schema of the differential hemolytic reactions, exhibited by V. parahaemolyticus, tissue infection vibrios, and nonpathogens on hamster, sheep, chicken, goose, and human blood is given. The patterns of hemolytic activity of these groups on special human blood-agar plates (Kanagawa hemolysis) resembled that seen on ordinary human blood-agar.